Monitoring changes in the genetic structure of Brown Tsaiya duck selected for feeding efficiency by microsatellite markers - Yi-Ying Chang; Hsiu-Chou Liu; Chih-Feng Chen (Animal Bioscience, 2023)
Objective Few studies have genetically monitored chickens over time, and no research has been conducted on ducks. To ensure the sustainable management of key duck breeds, we used microsatellite markers to monitor Brown Tsaiya ducks over time genetically. Methods The second, fourth, sixth to eighth generations of the Brown Tsaiya duck selected for feeding efficiency and control lines were included in this study to investigate the genetic variations, effective population size, population structure and the differentiation between populations over time with 11 microsatellite markers derived from Brown Tsaiya duck. Results The results showed there were a slight decrease in the genetic variations and an increase in within-population inbreeding coefficient (FIS) in both lines, but no consistent increase in FIS was observed in each line. The effective population size in the second and eighth generations was 27.2 for the selected line and 23.9 for the control line. The change in allele richness showed a downward trend over time, and the selected line was slightly lower than the control line in each generation. The number of private alleles (Np) in the selected line were higher than in the control line. Moderate differentiation was observed between the second and eighth generations in the selected line (FST = 0.0510) and the control line (FST = 0.0606). Overall, differentiation tended to increase with each generation, but genetic variation and structure did not change considerably after six generations in the two lines. Conclusion This study provides a reference for poultry conservation and helps to implement cross-generation genetic monitoring and breeding plans in other duck breeds or lines to promote sustainable management.